Sheep in wolf's clothing: host nestling vocalizations resemble their cowbird competitor's - Pagnucco, Katie (The Royal Society, 2008)
Nestlings of many avian brood parasites are virtuosos at mimicking host nestling vocalizations, which, like egg mimicry, presumably ensures acceptance by host parents. Having been accepted, parasitic nestlings then often exaggerate the aspects of the host's display to increase parental care. Host nestlings may, in turn, exaggerate their vocalizations to keep up with the parasite, though this possibility has not been evaluated. We experimentally parasitized song sparrow (Melospiza melodia) nests with a brown-headed cowbird (Molothrus ater) chick to evaluate how host nestlings respond. Vocalizations emitted from experimentally parasitized nests were higher in frequency, and louder, than those from unparasitized nests, consistent with the cowbird exaggerating its signalling. In response, host nestlings exaggerated the frequency and amplitude of their vocalizations, such that they resembled the cowbird's while they ‘scaled back’ on calls per parental provisioning bout. Sparrows in parasitized nests were fed equally often as sparrows in unparasitized nests, suggesting that exaggerating some aspects of vocalization while scaling back on others can help host nestlings confronted with a cowbird. Our results support the recently proposed hypothesis that signalling in parasitized nests involves a dynamic interaction between parasitic and host nestlings, rather than a one-way process of mimicry by the parasite.